1986
DOI: 10.1073/pnas.83.23.8839
|View full text |Cite
|
Sign up to set email alerts
|

Nuclease resistance and the enrichment of native nuclear acceptor sites for the avian oviduct progesterone receptor.

Abstract: High-affinity nucleoprotein acceptor sites for the avian oviduct progesterone receptor (PR) have been enriched by a combination of nuclease digestion and centrifugation. These enriched binding elements exhibited markedly enhanced PR binding on a per mass DNA basis compared to chromatin (20-to 25-fold) or dehistonized chromatin (4-to 5-fold). Electrophoretic analysis of the nuclease-resistant DNA showed that there is a set of DNA fragments of 100-150 base pairs that are protected from digestion. Excessive diges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…A number of groups have presented evidence that specific NHPs together with the DNA were in some way involved in specifically binding the hormone-receptor complex to the chromatin and that naked DNA was unable to bind purified steroid receptors (24)(25)(26)(27)(28). Unfortunately, all these studies used only bulk chromatin and did not examine the role of specific DNA sequences in receptor binding.…”
Section: Resultsmentioning
confidence: 99%
“…A number of groups have presented evidence that specific NHPs together with the DNA were in some way involved in specifically binding the hormone-receptor complex to the chromatin and that naked DNA was unable to bind purified steroid receptors (24)(25)(26)(27)(28). Unfortunately, all these studies used only bulk chromatin and did not examine the role of specific DNA sequences in receptor binding.…”
Section: Resultsmentioning
confidence: 99%
“…The nuclear mitotic apparatus protein (NuMA), first identified as a protein localizing on the spindle poles of mitotic cells, is a component of the nuclear matrix in interphase cells [Zeng et al, 1994;Harborth et al, 1999;Gribbon et al, 2002]. It has long been understood that steroid receptors associate with the nuclear matrix ligand-dependently [Hora et al, 1986;Barrack, 1987;Hu et al, 1994;Tang and DeFranco, 1996], and thus hypothesized that the nuclear matrix binding may play an important role in the regulation of steroid hormone receptor-mediated transcription. In the previous study, Stenoien et al [2000] visualized a nuclear matrix binding property of ERa using GFP-ERa, and showed that most of ligand-activated GFP-ERa was associated with the nuclear matrix by forming discrete clusters.…”
mentioning
confidence: 97%
“…Selective removal of the chromatin protein fraction which contains RBF-1 results in the loss of the highest affinity class of PR binding sites. When RBF-1 is reconstituted to avian genomic DNA, the specific binding of PR is regenerated [Spelsberg et al, 1984Schuchard et al, 1991a,b;Hora et al, 1986;Goldberger et al, 1987;Rejman et al, 19911. The RBF-1 has been purified to homogeneity from oviduct nuclei and characterized.…”
mentioning
confidence: 97%
“…Chromatin acceptor sites for the avian oviduct progesterone receptor (PR) have been studied extensively and found to consist of complexes of specific acceptor proteins tightly bound t o specific DNA sequences [Spelsberg et al, 1972[Spelsberg et al, , 1984[Spelsberg et al, , 1987a[Spelsberg et al, ,b, 1988Schuchard et al, 1991a,b;Pikler et al, 1976;Kon and Spelsberg, 1982;Hora et al, 1986;Goldberger et al, 1987;Goldberger and Spelsberg, 1988;Rejman et al, 19911. The specificity of this interaction is highlighted by in vivo and in vitro studies which demonstrate that the binding of PR to avian oviduct chromatin is not only saturable and high affinity [Spelsberg et al, 1983[Spelsberg et al, , 1984[Spelsberg et al, , 1987aPikler et al, 19761, but also receptor dependent [Pikler et al, 19761 and receptor specific [Spelsberg et al, 1987a,b;Kon and Spelsberg, 19821.…”
mentioning
confidence: 99%